Lacunary Statistical Convergence of Order alpha and Lacunary Strongly Summable Sequences of Order alpha of Generalized Difference Sequences - Et, Mikail; Sengul, Hacer; Cinar, Muhammed (E D P Sciences, 2018)
The notion of the alpha th order Delta(m)(i) - lacunary statistical convergence and alpha th order lacunary strongly (Delta(m)(i), p) - summable sequences was introduced by Altmok et al. [1]. They also gave significant inclusion correlation associated with the aforementioned sequence spces. In this paper, our aim is to exploit some other important relations between the given notions.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Lambda; Spaces